A inclusão escolar das crianças com autismo do Ciclo I do Ensino Fundamental: ponto de vista do professor - Afonso, Salete Regiane Monteiro [UNESP] (2014)
Discussions about inclusive education, present in schools and other realms of society, aim to provide access, retention of learners and qualified learning system, in order to meet all needs of children. The inclusive movement still generates many doubts, mainly concerning the practical alternatives. In a specific situation, with autistic students, there are other barriers, as difficulty in socialization, communication and behavior, which are essential conditions for the educational development. Nonetheless, it has been observed that the amount of students with autism, enrolled in regular schools, is increasing. It becomes necessary to search for new and more effective strategies, in order to guarantee the right to education. Therefore, the present study aimed to investigate the knowledge of elementary school teachers about three important aspects: the condition of autism, the inclusive education of these students and the pedagogical actions applied in classroom experiences. For that reason, nine teachers of elementary schools - 1st to 4th grades were interviewed. They were employees of the Education Municipal Secretary of a town located in the interior of São Paulo state and had some working experience with students with autism, enrolled in regular classes of regular education, during the year of 2011. In reference to the instrument, the semi-structured interview was applied and the sequence followed the three aspects described above. The questions were elaborated based on the theory studied, and they were submitted to the appreciation of three foreign judges. The results demonstrate the necessity of information which conciliates theory and practice, because it was observed, from the sample studied, that theoretical knowledge should be aligned with practical experience. This fact may help to fade away some myths related to the people with autism and consequently there is higher possibility of...